Reactive perforating collagenosis - Yadav Mukesh; Sangal B; Bhargav Puneet; Jai P; Goyal Mukul (Wolters Kluwer Medknow Publications, 2009)
Reactive perforating collagenosis is a rare cutaneous disorder of unknown etiology. We hereby describe a case of acquired reactive perforating collagenosis in a patient of diabetes and chronic renal failure.